Design of Portable Beverage Cooler Using One Stage Thermoelectric Cooler (TEC) Module - Azridjal Aziz; Rahmat Iman Mainil; Afdhal Kurniawan Mainil; Sayfri Syafri; Muhammad Faizal Syukrillah (Aceh International Journal of Science and Technology, 2017)
The Portable Beverage Cooler (PBC) has been designed to satisfy the need of cooler apparatus that could be carried easily. The utilization of this apparatus was intended to minimize the environmental damage affected by vapour compression refrigeration system using CFCs Refrigerant. The peltier effect from thermoelectric module was utilized in this PBC and called as Thermoelectric Cooler (TEC). Furthermore, heat-sink and fan were needed to ensure the cooling effect continously worked. To achieved the objectives of this machine (portable, environment-friendly, low watt, affordable), the design consideration are heat load, insulating material, weight of components, electric consumption, and dimension of the cooling box.  The results of the design shows the PBC cooling box dimension is 6 cm x 6.5 x 15 cm. The insulation of the PBC cooling box are polyurethane foam and polystyrene expanded with thickness 6 mm and 5.3 mm, respectively. The alumunium plate was applied as inner wall to enhance the cooling capacity of cooling room temperature. In this PBC was used one stage of TEC that could yield cooling room temperature until 15 oC in 30 minutes operation by consuming 20 W of electricity.